A Conceptual Framework for transition modelling. (12th May 2008) - Haxeltine, Alex; Whitmarsh, Lorraine; Bergman, Noam; Rotmans, Jan; Schilperoord, Michel; Kohler, Jonathan
This paper presents a Conceptual Framework (CF) for analysing and simulating transition dynamics (or radical systemic innovation) that is broadly consistent with both empirical evidence and current theorising about transitions. The framework distinguishes between a dominant socio-technical regime and a number of socio-technical niches. The central feature of the framework is to describe how niches and regime interact to produce a transition dynamic involving either a transformation or a total overthrow of the dominant regime. We base the analysis on reviews of patterns observed in historical transitions, and provide a framework for analysing the processes involved in producing future 'sustainability transitions'.